Plant tissue culture concepts and laboratory exercises (CRC press, 1996)
The book provides historical perspectives, state-of the art techniques and methods, along with future advances and applications. Each topic is supported by reliable laboratory exercises. Laboratory exercises provide complete step-by-step instructions including anticipated results and thought-provoking questions